Analysis Of Factors Affecting Debt Policy - Sindy Larasasti; Nabila Rahmadayanti; Suci Ramadhani; Marcella Chintya Manao; An Suci Azzahra (CV. AFDIFAL MAJU BERKAH, 2025)
Debt policy is one of the crucial aspects in financial management both at the country and company level. Understanding the factors that have an impact on debt policy is very important by collecting and processing data on 57 manufacturing companies listed on the IDX and focusing on variables of profitability, liquidity, asset structure, and company growth. The research method used is panel data regression analysis. The results of the fixed effect model selection test resulted from the Chow test and the Hausman test. Profitability has a negative and significant impact on debt policy, company growth has a positive and significant influence on debt policy. While liquidity and asset structure have no significant impact. With a high level of significance, the independent variables affect DER jointly, as shown by simultaneous testing with the F test. The Adjusted R Square result of 67.6914% supports the idea that the model including the independent variables is responsible for most of the variation in DER. Nonetheless, the last variation of 32.3086% is accounted for by other variables not discussed from this study